Stress-strain analysis of a cylindrical pipe subjected to a transverse load and large deflections - R. M. Guedes (2009)
The increased use of polymers and reinforced polymers in civil construction applications originated elegant structures with a high specific strength and stiffness. The mechanical performance improved significantly in comparison with traditional materials; however, the structural engineers face new challenges. The high strength compared with the stiffness of these new materials allows large deformations without failure or damage, especially in large structures. The classical theories, i.e. based on small deformations, became no longer valid and corrections must be used. The aim of this work was to show this occurrence in a practical case, used in civil engineering construction. For that purpose a glass-fiber reinforced (GRP) buried pipe under a transverse load was analyzed. Strains experimentally measured and FEM analyses are used to verify the phenomenon. In this case, the relation between the maximum deflection and the maximum hoop strain was no longer linear as predicted by the small deformation theory. A simple approach using deformation components based on finite deformations theory was proposed and assessed. Although this approach, which has an analytical integral solution, does not predict accurately the nonlinear phenomena it allowed a dimensionless parametric study of the problem. A simple correction of this approach is proposed and assessed.